Gadget dan Speech Delay: Kajian Perkembangan Kemampuan Berbahasa Anak - Hidayatul Umah, Restu Yulia (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2017)
Language is a social act. The development of speech and language is the ability of the child to respond the voice heard, convey his wishes, following the orders given, and so on. Early childhood shows rapid increase and complexity in speech and language development. Speech delay is one of the causes of developmental disorders in child language. The term speech delay in a child is an abnormality in a childs speech when compared to his or her age. Using excessive gadgets at the early age is a factor that makes the child more a passive listener. Communicate only one direction, ie respond. The child will play a role more as a recipient without having to digest and process the incoming information. To avoid the possibility of increased speech delay, therefore it is very important to prevent and limit toddlers when using the gadget. This paper is a conceptual study of how the process of language development in early childhood and how the gadget can lead to the negatif effect against it.